2017
DOI: 10.1021/acs.jpcc.6b12501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phase Transitions on Thermal Depoling in Lead-Free 0.94(Bi0.5Na0.5TiO3)–0.06(BaTiO3) Based Piezoelectrics

Abstract: 0.94­(Bi0.5Na0.5TiO3)–0.06­(BaTiO3) (BNTBT) is a potential lead-free piezoelectric candidate to replace lead-based PZT ceramics. The thermal depoling temperature sets the upper limit for the high temperature application of piezoelectric materials. Recently, an interface model was proposed to explain the good resistance to thermal depoling of BNTBT-ZnO composite. However, we found that the presence of ZnO was not limited to the interface, but contributed intrinsically to the BNTBT lattice. This played a critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 32 publications
2
54
0
1
Order By: Relevance
“…The variation of (111) diffraction peaks indicate that the addition of NN tends to decrease the fraction of rhombohedral phase in BNT–BA ceramics. As well known, the rhombohedral R3c structure is polar, with parallel displacement of A‐ and B‐site cations along (111) direction . Therefore, it can be inferred that increasing the NN content will result in the disruption of the long‐range polar phase.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…The variation of (111) diffraction peaks indicate that the addition of NN tends to decrease the fraction of rhombohedral phase in BNT–BA ceramics. As well known, the rhombohedral R3c structure is polar, with parallel displacement of A‐ and B‐site cations along (111) direction . Therefore, it can be inferred that increasing the NN content will result in the disruption of the long‐range polar phase.…”
Section: Resultsmentioning
confidence: 84%
“…It can be observed that all the ε r − T curves show weak frequency dispersion well below T FR , which is related to the electric‐field induced long‐rang ferroelectric (FE) order . As the temperature increases to T FR , the induced FE order can be transformed into nanodomains or PNRs as evidenced by the stronger frequency dispersion of dielectric constant . With further heating at T m , the ergodic phase is changed into paraelectric phase .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the maximum negative field was applied, the weakly polar phase changed again to a polar phase that corresponded to the peak at − E F . Similarly, upon reversing the applied field, the polar phase transformed back again to a weakly polar phase that corresponded to the peak at − E B . The other compositions that contained either a Ti deficiency or excess Ti exhibited saturated P ‐ E loops with two typical domain switching current peaks at the coercive field ± E c .…”
Section: Resultsmentioning
confidence: 97%